Offspring of Prenatal IV Nicotine Exposure Exhibit Increased Sensitivity to the Reinforcing Effects of Methamphetamine - Harrod, Steven B.; Lacy, Ryan T.; Morgan, Amanda J. (Frontiers in Pharmacology, 2012)
Maternal smoking during pregnancy is associated with increased substance abuse in offspring. Preclinical research shows that in utero exposure to nicotine, the primary psychoactive compound in tobacco smoke, influences the neurodevelopment of reward systems and alters motivated behavior in offspring. The present study determined if prenatal nicotine (PN) exposure altered the sensitivity to the reinforcing and aversive effects of methamphetamine (METH) in offspring using a low dose, intravenous (IV) exposure method. Pregnant dams were administered nicotine (0.05 mg/kg/injection) or prenatal saline (PS) 3×/day on gestational days 8-21, and adult offspring were tested using METH self-administration (experiment 1) or METH-induced conditioned taste aversion (CTA; experiment 2) procedures. For METH self-administration, animals were trained to respond for IV METH (0.05 mg/kg/injection; fixed-ratio 3) and they were tested on varying doses the reinforcer (0.0005-1.0 mg/kg/injection). For METH CTA, rats received three saccharin and METH pairings (0, 0.3, or 0.5 mg/kg, sc) followed by fourteen daily extinction trials. Experiment 1: PN and PS animals exhibited inverted U-shaped dose-response curves; however, the PN animal’s curve was shifted to the left, suggesting PN animals were more sensitive to the reinforcing effects of METH. Experiment 2: METH CTA was acquired in a dose-dependent manner and the factor of PN exposure was not related to the acquisition or extinction of METH-induced CTA. There were no sex differences in either experiment. These results indicate that adult offspring of IV PN exposure exhibited altered motivation for the reinforcing effects of METH. This suggests that PN exposure, via maternal smoking, will alter the reinforcing effects of METH during later stages of development, and furthermore, will influence substance use vulnerability in adult human offspring.